Low-temperature graphitization of poly(acrylonitrile) densely grafted onto a silica core surface. (26th May 2021) - Yamazaki, Shohei; Yoshida, Keiichiro; Matsumoto, Hidetoshi; Tokita, Masatoshi
Abstract: This study realized a graphitic structure from the low-temperature carbonization of poly(acrylonitrile) (PAN) grafted onto a nanoparticle's surface at a density of 0.3 chains nm −2 . The temperature was increased up to 800 °C, which is 2000 °C lower than that in conventional graphitization processes. Two types of PAN-grafted nanoparticles with different core diameters of 30 and 150 nm were prepared and cast from a solution into films. The films comprised cores arranged in a face-centered cubic (FCC) lattice, which was maintained after the carbonization, albeit with shortened lattice sides. Elution of the silica cores by hydrofluoric acid etching produced carbonized PAN films with FCC-arranged pores. The carbonized PAN exhibited X-ray diffraction (XRD) peaks associated with the graphitic structure. Conversely, the same carbonization of similar PAN-grafted nanoparticles with a lower grafting density of 0.05 chains nm −2 produced similar porous carbon films, but the graphitic structure was not evidenced by the associated XRD patterns. These results confirm that lower-temperature graphitization requires dense grafting of PAN chains onto a solid surface. Graphical abstract: Image 1 Highlights: PAN is grafted onto SiO2 particles at 0.3 chains nm − 2 by surface-initiated ATRP. PAN-grafted particles in the solution-cast film arrange the cores in an FCC lattice. The grafted PAN is carbonized at 800 °C, forming a graphitic structure in part. Elution of the SiO2 cores gives a carbon film with FCC-arranged pores.